The Inception Workshop Report. Transforming the Rules of the Game: Gendered Liveability in Peri-urban Dhaka - International Potato Center; Bangladesh Agricultural University (2021)
The inception workshop on “Transforming the Rules of the Game: Gendered Liveability in Peri-urban Dhaka” was held on 20 December 2021 in Dhaka, Bangladesh, to introduce the key partners to this project, and to share ideas, knowledge, and experiences that could helpfully inform the execution of the research. Thirty-three people (50% women) participated in this workshop, including government officers, local and international NGO representatives, university staff and private sector employees from the garment industry. Collectively, this group represented expertise in many subjects such as nutrition, food systems, environment, and urban development. The participants shared some practical approaches towards improving the living environment and food/water/nutrition for poor residents in urban areas. This workshop highlighted the importance of cross-sectoral collaboration with diverse institutions to understand the government’s priorities and interests. This report outlines key points and messages including feedback from project partners. The links to key documents are also included in this report.